Meiotic deviations and endoreplication lead to diploid oocytes in female hybrids between bighead catfish (Clarias macrocephalus) and North African catfish (Clarias gariepinus) - Dedukh, Dmitrij; Lisachov, Artem; Panthum, Thitipong; Singchat, Worapong; Matsuda, Yoichi; Imai, Yukiko; Janko, Karel; Srikulnath, Kornsorn (Frontiers in Cell and Developmental Biology, 2024)
Introduction Reproductive isolation and hybrid sterility are mechanisms that maintain the genetic integrity of species and prevent the introgression of heterospecific genes. However, crosses of closely related species can lead to complex evolution, such as the formation of all-female lineages that reproduce clonally. Bighead catfish (Clarias macrocephalus) and North African catfish (C. gariepinus) diverged 40 million years ago. They are cultivated and hybridized in Thailand for human consumption. Male hybrids are sterile due to genome-wide chromosome asynapsis during meiosis. Although female hybrids are sometimes fertile, their chromosome configuration during meiosis has not yet been studied. Methods We analyzed meiosis in the hybrid female catfish at pachytene (synaptonemal complexes) and diplotene (lampbrush chromosomes), using immunostaining to detect chromosome pairing and double-stranded break formation, and FISH with species-specific satellite DNAs to distinguish the parental chromosomes. Results More than 95% of oocytes exhibited chromosome asynapsis in female hybrid catfish; however, they were able to progress to the diplotene stage and form mature eggs. The remaining oocytes underwent premeiotic endoreplication, followed by synapsis and crossing over between sister chromosomes, similar to known clonal lineages in fish and reptiles. Discussion The occurrence of clonal reproduction in female hybrid catfish suggests a unique model for studying gametogenic alterations caused by hybridization and their potential for asexual reproduction. Our results further support the view that clonal reproduction in certain hybrid animals relies on intrinsic mechanisms of sexually reproducing parental species, given their multiple independent origins with the same mechanism.